"Edge-on" MOSkin detector for stereotactic beam measurement and verification. (January 2017) - Jong, Wei Loong; Ung, Ngie Min; Vannyat, Ath; Jamalludin, Zulaikha; Rosenfeld, Anatoly; Wong, Jeannie Hsiu Ding
Highlights: The suitability of an "Edge-on" MO Skin detector was determined. The "Edge-on" MO Skin detector concurred with EBT2 film measurements in terms of dose profiles and output factors. The "Edge-on" MO Skin detector and EBT2 film measured doses concurred with the TPS calculated dose for SRS and SRT. The "Edge-on" MO Skin detector is a suitable tool for dose verification in small field dosimetry. Abstract: Dosimetry in small radiation field is challenging and complicated because of dose volume averaging and beam perturbations in a detector. We evaluated the suitability of the "Edge-on" MO Skin (MOSFET) detector in small radiation field measurement. We also tested the feasibility for dosimetric verification in stereotactic radiosurgery (SRS) and stereotactic radiotherapy (SRT). "Edge-on" MO Skin detector was calibrated and the reproducibility and linearity were determined. Lateral dose profiles and output factors were measured using the "Edge-on" MO Skin detector, ionization chamber, SRS diode and EBT2 film. Dosimetric verification was carried out on two SRS and five SRT plans. In dose profile measurements, the "Edge-on" MO Skin measurements concurred with EBT2 film measurements. It showed full width at half maximum of the dose profile with average difference of 0.11 mm and penumbral width with difference of ±0.2 mm for all SRS cones as compared to EBT2 film measurement. For output factor measurements, a 1.1% difference was observed between the "Edge-on" MO Skin detector and EBT2 film for 4 mm SRS cone. The "Edge-on" MO Skin detector provided reproducible measurements for dose verification in real-time. The measured doses concurred with the calculated dose for SRS (within 1%) and SRT (within 3%). A set of output correction factors for the "Edge-on" MO Skin detector for small radiation fields were derived from EBT2 film measurement and presented. This study showed that the "Edge-on" MO Skin detector is a suitable tool for dose verification in small radiation field.